Effect of Fluid Supplementation on the Duration of Phototherapy - Morshed, Jesmeen; Shahidullah, Mohammod; Motanabbi, Mahbub; Dey, Sanjoy Kumer (Bangladesh Journal of Child Health, 2018)
Background: Hyperbilirubinemia or jaundice is a common condition found in neonates. If intervention is not initiated in case of gradually increasing hyperbilirubinemia may progress to develop kernicterus. Subclinical dehydration (Serum osmolality >290 mosm/kg) due to evaporative losses and poor intake of breast milk can lead to an increased incidence and exaggeration of jaundice in newborns leading to longer duration of phototherapy. Adequate hydration and good urine output improve the efficacy of phototherapy. Objective: To evaluate the effect of fluid supplementation on the duration of phototherapy. Methods: This was a randomized controlled trial conducted in NICU of BSMMU, Dhaka, Bangladesh. Sixty-four term neonates with severe nonhemolytic hyperbilirubinemia (TSB >18 mg/dl to <25 mg/dl) was included for study. The subjects were randomized to a case group (Group-I) (intravenous fluid supplementation) and control group (Group-II). Result: The rate of fall of S. bilirubin per hour at 6 hrs, 12 hrs, 24 hrs and 48 hrs after admission in intravenous fluid receiving group was more than the control group and it was statistically significant. Duration of Phototherapy in babies receiving extra IV fluid (Group-I) was also significantly less than those who did not receive IV fluid. Conclusion: Increased fluid supplementation during treatment in severe non-hemolytic hyperbilirubinemic patient decreases the duration of phototherapy. Bangladesh J Child Health 2017; VOL 41 (2) :92-95